Practice Acceptance and Label Rejection: Social Ambivalence toward Islam Nusantara in Minangkabau, Indonesia - Andri Ashadi; Wakidul Kohar; Sefriyono Sefriyono; Sarwan Sarwan; Danil Folandra (International Journal of Islamic Khazanah, 2026)
This study examines the ambivalent reception of Islam Nusantara in Minangkabau, West Sumatra, where local Islamic practices associated with cultural accommodation remain socially accepted, while the label Islam Nusantara is strongly contested. The study is important because it addresses a paradox in Minangkabau religious life: practices such as maulid, badikia, grave pilgrimages, communal recitations, malamang, and post-death rituals are embedded in local Islamic traditions, yet become suspicious when explicitly associated with Islam Nusantara. Using a qualitative approach, this research draws on semi-structured interviews with 16 informants, including ulama, Nahdlatul Ulama leaders and activists, ninik mamak, and community members in Padang Pariaman and Pasaman Barat. The study also analyzes online news reports, institutional statements, and public discourse materials published between 2018 and 2022. Data were examined through thematic analysis using Jan Hajda’s theory of ambivalence. The findings show three main patterns: first, the coexistence of practice acceptance and label rejection; second, the role of ABS–SBK as a contested interpretive field rather than a fixed philosophy of Islam and adat; and third, the production of threat narratives through institutional authority, elite framing, digital circulation, and trusted informal networks. This study contributes to the literature on Islam Nusantara, local Islam, and religious authority by showing that resistance to a religious discourse may emerge not from the substance of practice, but from the stigma, authority, and symbolic burden attached to its label.